Effective BUMDes Management Strategies to Improve Village Economy in Naga Dolok Village, Simalungun Regency - Sarida Sirait; Kalvin Sinaga (Institute of Computer Science (IOCS), 2020)
The purpose of this study is to formulate a strategy in terms of BUMDes management in the context of improving the economy of the Naga Dolok village, Simalungun Regency. Increasing the community's economy that encourages rural economic development, increasing creativity and improving the community's economy, encouraging the growth and development of the informal sector micro-enterprise, increasing the income and welfare of the village community, increasing the village's original income. The research method used in this study is a qualitative research method with direct data collection techniques for conducting interviews, observations, and distributing questionnaires. In addition to qualitative analysis, the data collected will be analyzed by SWOT Analysis. The results of this study are expected to provide technical solutions that manage BUMDes so that financial problems can be resolved by the community well and BUMDes in this village can make a good contribution to the community.